Paradoxes aesthetic interpretation of the relationship of form and content in art - Мізіна, Л.Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
In the article the metamorphosis meanings categories of form and content in the history of aesthetics: semantic polysemy, the substitution of meanings and terms, identification of the concepts of "form" and "means" an eclectic mix of different meanings in the same notion.